Síntese e caracterização espectroscópica de compostos de coordenação contendo o ligante dipirido [3,2-f: 2,3-h] quinoxalina 2,3 ditetrazol - Ferreira, Rafael Caruba [UNIFESP] (2016)
The work had two main lines: an experimental and a computacional one. The experimental work comprehended: synthesis of the liganddipirido [3,2-f: 2?,3?-h] quinoxalina ? 2,3 ditetrazol(dpq-dTzol), synthesis of coordination compounds with Fe(II), Zn(II) , Cu(II) and Ni(II), structural confirmation by nuclear magnetic resonance of 1H and 13C, mass spectrometry, vibrational spectroscopic analysis through infrared, Raman and resonance Raman spectroscopies, and analysis of electronic transition in the UV-Visible spectroscopy. Already the computacional aspect comprehended the use of calculations using the Density Functional Theory with methods B3LYP and M06-2X, essentially to estimate the equilibrium geometries, energies and shapes of molecular orbitals, compute vibrational, electronic and nuclear magnetic resonance spectra. The metal-to-ligand charge-transfer was studied, using the molecular orbitals with the spectroscopic results and we concluded that only the coordination compounds with Fe(II) show this phenomenon. The computing data were compared with the experimental data too.